Treatment-induced changes in the androgen receptor axis: Liquid biopsies as diagnostic/prognostic tools for prostate cancer. (15th February 2018) - Prekovic, S.; Van den Broeck, T.; Moris, L.; Smeets, E.; Claessens, F.; Joniau, S.; Helsen, C.; Attard, G.
Abstract: Prostate cancer progression and treatment relapse is associated with changes in the androgen receptor axis, and analysis of alternations of androgen receptor signaling is valuable for prognostics and treatment optimization. The profile of androgen receptor axis is currently obtained from biopsy specimens, which are not always easy to obtain. Moreover, the information acquired only provides a snapshot of the tumor biology, with strict spatial and temporal limitations. On the other hand, circulation is easily accessible source of both circulating tumor cells and circulating tumor DNA, which can be sampled at numerous time points. This Review will explore the potential use of androgen receptor axis alternations detectable in the blood in therapeutic decision-making and precision medicine for advancing metastatic castration-resistant prostate cancer. Highlights: Prostate cancer progression and treatment relapse is associated with changes in the androgen receptor axis. Circulation is easily accessible source of both circulating tumor cells and circulating tumor DNA. Androgen receptor axis alternations detectable in blood could be of use in therapeutic decision-making for prostate cancer.